FTIR: A novel method for identifying fish gut contents - Abolfazl Aminimehr; Mohammad Amini Chermahini; Laleh Moosavi Dehmoordi (تغذیه آبزیان)
Introduction: If the composition of ingested food changes along the digestive tract in such a way that fish feces reflect the initial composition of the consumed food, there would be no need to sacrifice fish to identify the contents of their gut. Instead, one could determine the fish's diet in nature or fish farms simply by analyzing their feces. The aim of this study was to investigate different foods and their composition alterations along the digestive tract using FTIR spectroscopy for the first time, to evaluate the possibility of determining an index to identify the consumed food using the resulting feces.Materials and methods: Five different types of food were used to feed tilapia: common carp-formulated feed, Gammarus, bloodworm, a combination of bloodworm-Gammarus (1:1), and wheat. Ten fish were placed in each tank. Feeding was conducted for 10 days, twice daily. After 7 hours of the last feeding, the fish were euthanized using clove powder. The feces were collected from the end of the intestine, preserved in liquid nitrogen, then freeze-dried and homogenized. The samples were analyzed using the ATR-FTIR.Results and discussion: By comparing the obtained wavelengths, specific patterns were identified between the ingested food and the resulting feces. The ratio of fats in the feed and the resulting feces showed the least change, making fats as one of the groups that can be used to distinguish samples. Based on the results, foods of animal- or plant-origin, i.e., bloodworm, Gammarus, and wheat, and the feces resulting from them, can be easily distinguished from each other and from the formulated feed. However, the formulated feed, which is a mixture of various plant and animal-derived materials, and its resulting feces were not as distinguishable.Conclusion: According to the results, it seems that the FTIR will be practical and reliable method to identify foods used by fish in aquaculture or nature using fish feces. Probably, in the latter case, it will be easier to identify, because in nature, more uniform food items (plant or animal sources) are usually consumed.